Factors that influence a patient’s decision to engage in genetic research - Almutairi, Amal; Alqubaishi, Fatimah Abdulrahman; Alsolm, Ebtehal A.; Binowayn, Albandari; Almohammad, Rania; Wani, Tariq; Ababtain, Aljohara; Alkadi, Udai; Alrashed, May M.; Althagafi, Malak; Abu-Safieh, Leen (Frontiers in Public Health, 2023)
Introduction: The most challenging step in clinical research studies is patient recruitment. Many research studies do not reach their targets because of participant rejection. The purpose of this study was to assess patient as well as the community knowledge, barriers, and motivation to participate in genetic research. Methods: A cross-section study was conducted between September 2018 and February 2020 using face-to-face interviews with candidate patients from outpatient clinics at King Fahad Medical City (KFMC), Riyadh, Saudi Arabia. Also, the study was conducted using an online survey designed to assess the community’s knowledge and willingness to participate in genetic research studies. Result: In total, 470 patients were interviewed for this study, with 341 being successfully recruited from the face to face interview, and the other patients being refused owing to time constraints. The majority percentage of the respondents were females. The respondents’ mean age was 30, and 52.6% reported having a college degree. The survey results from 388 participants illustrated that around 90% of the participants, participated voluntarily due to a good understanding of genetics studies. The majority held positive attitudes toward being part of genetic research, which exceeded the reported motivation score of >75%. The survey indicated that >90% of individuals were willing to participate to acquire therapeutic benefits or to receive continued aftercare. However, 54.6% of survey participants were worried about the side effects and the risks involved in genetic testing. 71.4% of people rejected participating due to their lack of genetic research knowledge. Conclusions: Respondents reported relatively high motivation and knowledge for participation in genetic research. However, study participants reported "don’t know enough about genetic research" and "lack of time during clinic visit" as a barrier for participation in genetic research.